Predictors of Pancreatitis Among Patients with Inflammatory Bowel Disease Treated with Vedolizumab: Observation from a Large Global Safety Database - Joe F. Wernicke; Tatsiana Verstak; Tianming Zhang; William Spalding; Laurie Lee; Yue Cheng; Alicia Ademi (Adis, Springer Healthcare, 2023)
Abstract Background Patients with inflammatory bowel diseases (IBDs) are at increased risk of pancreatitis. Data from a global safety database (GSD) were queried to identify risk factors for pancreatitis in vedolizumab-treated patients with IBD. Methods Takeda's GSD was retrospectively queried for case reports (CRs) of adverse events (AEs) following vedolizumab treatment, from licensure (May 20, 2014) through March 31, 2021. Unsolicited and solicited CRs of pancreatitis were coded using the Medical Dictionary for Regulatory Activities (MedDRA) High-Level Term "Acute and chronic pancreatitis." To examine factors associated with severe pancreatitis, serious CRs (serious AEs [SAEs]) were compared with SAEs from a comparator group of 600 random non-pancreatitis AEs. Comparisons were performed using t, χ 2, and Fisher's exact tests. Logistic regression was performed to adjust for covariates allowing backward selection. Results In total, 196 patients reported pancreatitis in > 700,000 patient-years of vedolizumab exposure. Pancreatitis was serious in 195 patients (99.5%), and non-pancreatitis AEs were serious in 195 of 600 (32.5%) in the random comparator group. In the pancreatitis group, 17 patients (8.7%) had a known history of pancreatitis versus none in the random comparator group. Younger age, vedolizumab indication of ulcerative colitis, concomitant medications (with a risk for pancreatitis), pancreatitis history, and comorbid conditions (especially ongoing pancreatitis) were associated with development of severe pancreatitis. Conclusions These analyses identified factors associated with pancreatitis SAEs in patients with IBD treated with vedolizumab, but do not suggest an increased risk of pancreatitis with vedolizumab. These findings will help inform which patients treated for IBD might have an elevated risk, regardless of treatment.